Potensi Culex quinquefasciatus sebagai Vektor Filariasis dan Kondisi Lingkungan di Kota Pekalongan - Nurjazuli Nurjazuli; Nikie Astorina Yunita Dewanti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2021)
Pekalongan City was still an endemic area of Lymphatic Filariasis (LF). Twice cycles ofMass Drug Administration (MDA) had been implemented, but the Microfi laria rate (Mf rate) wasstill more than 1%. This observational research aimed to study the potential of Culex quinquefasciatusas a vector of LF in Pekalongan City. A Cross-sectional design was chosen as an approach in compilinginformation related to environmental factors and mosquitoes. The population of this research washouses located in Jenggot and Kertoharjo village with thirty-one houses, located around fi lariasiscases, purposively selected as samples. Variables studied in this research were environmental factorsand mosquito vectors. Data collection using observation, and laboratory examination throughmosquito dissection. Data would be analyzed descriptively. This study found that there were 8 Culexquinquefasciatus tested positive L3 fi larial worm (infective rate 4.39%). There were 74.2% of houseshad mosquitoes’ breeding sites around them. The breeding sites were found at domestic waste disposal,drainage in front of the house, and infi ltration well for liquid waste. As much as 86.2% of the breedingsites contained mosquito larvae. This research concluded that Cx. quinquefasciatus was confi rmedpositive fi laria worm thus establish as mosquito vector for Lymphatic Filariasis in Pekalongan City.The breeding sites related to the mosquito development were small water bodies, drainage in front ofand around the house.